Optimization of the Online SIM Program in Improving SIM Issuance Services at Bogor City Police Resort - Aditama, Muhammad (Advances in Police Science Research Journal, 2024)
Research in background is in this revolution industry 4.0, technology become a lifestyle to fulfill society basic needs. In line with president’s and chief of national police officer’s work program, Korlantas Polri created a program based on technology called SIM (driver’s license) Online. The purpose of this research is to describe the implementations of SIM Online program, to know some factors that influence the implementations of SIM Online and to describe efforts that already made to optimalize the implementations of SIM Online in Polresta Bogor Kota. The research concepts are service excellence concept, driver’s license concept that contained in article 77 paragraph 1 of traffic law number 22 year 2009, and information technology concept. The theories are management theory and public service theory. This research use qualitative method with descriptive analytics techniques. Data source from primary and secondary data that obtained from interview, observation and document study. Research location in satpas online Polresta Bogor Kota. Data validity including data reduction, data present, and conclusion making and verification. The implementation of SIM Online is analyze with article 77 paragraph 1 of traffic law number 22 year 2009 and management theory and based on standard operational procedure. But there are still lacks in somethings. For example, lack of socialization, the society lack in technology skill, and the maintenance of materials and machines. Factors that influence is analyze with elements in management theory. Need to optimalize in some factors like in human resources, money, and machines. Efforts that already did are one gate system, first in first out system, and other facilities that support the service. Conclusion of the implementation of SIM Online is already good based on standard operational procedure, but there are still lacks in some factor. Suggestion to optimalize SIM Online is to socialize more about SIM Online Program.